Tổng quan nghiên cứu về các yếu tố ảnh hưởng đến sự hình thành và phát triển định hướng giá trị nghề nghiệp của học sinh trung học phổ thông - Ngô , Thanh Thủy (Tạp chí Giáo dục, 2023)
The 2018 General Education Curriculum includes vocational education content to provide high school students with accurate and appropriate career orientations. Based on a theoretical review, the study generalizes the subjective influencing factors (including personal characteristics, age, positivity, tendencies, personal preferences, etc.) and objective factors (including societal needs, career-oriented education in schools, family education and living conditions, and local cultures) affecting the career value orientation among high school students. The influence of these factors varied at different levels with each individual. Thus, the orientation of an individual’s professional values is unique for each individual and imbued with characteristics of local cultures and communities. This study also points out further research directions on the current situation of influencing factors such as age, gender, and regional approaches at high school level.